AGO2 promotes telomerase activity and interaction between the telomerase components TERT and TERC. (27th December 2018) - Laudadio, Ilaria; Orso, Francesca; Azzalin, Gianluca; Calabrò, Carlo; Berardinelli, Francesco; Coluzzi, Elisa; Gioiosa, Silvia; Taverna, Daniela; Sgura, Antonella; Carissimi, Claudia; Fulci, Valerio
Abstract: Telomerase reverse transcriptase (TERT) and telomerase RNA component (TERC) constitute the core telomerase enzyme that maintains the length of telomeres. Telomere maintenance is affected in a broad range of cancer and degenerative disorders. Taking advantage of gain‐ and loss‐of‐function approaches, we show that Argonaute 2 (AGO2) promotes telomerase activity and stimulates the association between TERT and TERC. AGO2 depletion results in shorter telomeres as well as in lower proliferation rates in vitro and in vivo . We also demonstrate that AGO2 interacts with TERC and with a newly identified sRNA ( terc ‐sRNA), arising from the H/ACA box of TERC. Notably, terc ‐sRNA is sufficient to enhance telomerase activity when overexpressed. Analyses of sRNA‐Seq datasets show that terc ‐sRNA is detected in primary human tissues and increases in tumors as compared to control tissues. Collectively, these data uncover a new layer of complexity in the regulation of telomerase activity by AGO2 and might lay the foundation for new therapeutic targets in tumors and telomere diseases. Synopsis: AGO2 promotes telomerase activity and the interaction between TERT and TERC. AGO2 further binds TERC and a small RNA derived from TERC, terc ‐sRNA, that also stimulates telomerase activity. AGO2 depletion results in telomere shortening, impairment of association between TERT and TERC RNA and decrease of telomerase activity. AGO2 interacts with TERC RNA via CR4/CR5 and TBE domains and binds a small RNA ( terc ‐sRNA), which arises from the 3′end of TERC. Overexpression of terc ‐sRNA stimulates telomerase activity. Abstract : AGO2 promotes telomerase activity and the interaction between TERT and TERC. AGO2 further binds TERC and a small RNA derived from TERC, terc ‐sRNA, that also stimulates telomerase activity.